2006
DOI: 10.2754/avb200675010123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Dressing Percentage of 3-year-old Experimental Scaly Crossbreds of the Common Carp (Cyprinus carpio, Linnaeus 1758) in Relation to Sex

Abstract: The aim of the present study was to compare dressing percentages, with relation to sex, of three bisexual groups of hybrid carp, i.e. Hungarian mirror carp and Northern mirror carp (M2 × M72), the hybrid line of Pfierov scaly carp and Northern mirror carp (PS × M72), the hybrid line of Pfierov scaly carp and Ropsha scaly carp (PS × ROP), and the pure line of Pfierov scaly carp (PS) in harvest size (K 3 ). There were practically no differences in growth variables of male and female carp between the pure line PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The same levels of AA in hard roes of experimental female fish (PS, PS × M72, PS × ROP) and hard roes of control hybrid females M2 × M72 were found in three cases only (Arg, Ser, Glu). The reason for differences the frequently found in the content of other AA in hard roes probably lies in the different stages of their gonadogenesis, which are related to proven differences in growth capabilities between the groups of carp studied, and the differences in the weight of hard roes and the GSI♀ value (Buchtová et al 2006a, b). It was interesting to note that roes of experimental female carp (PS, PS × M72, PS × ROP) contained, besides the non‐essential Glu, mainly Val, whereas hard roes of control female carp (M2 × M72) contained, besides Glu, mainly Gly.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The same levels of AA in hard roes of experimental female fish (PS, PS × M72, PS × ROP) and hard roes of control hybrid females M2 × M72 were found in three cases only (Arg, Ser, Glu). The reason for differences the frequently found in the content of other AA in hard roes probably lies in the different stages of their gonadogenesis, which are related to proven differences in growth capabilities between the groups of carp studied, and the differences in the weight of hard roes and the GSI♀ value (Buchtová et al 2006a, b). It was interesting to note that roes of experimental female carp (PS, PS × M72, PS × ROP) contained, besides the non‐essential Glu, mainly Val, whereas hard roes of control female carp (M2 × M72) contained, besides Glu, mainly Gly.…”
Section: Discussionmentioning
confidence: 96%
“…The authors have demonstrated the existence of statistically significant differences in the quantitative representation of certain AA in edible parts of the common carp depending on the type of hybrid and line ( P <0.05 and P <0.01 respectively), which may be related to changes in their specific genetic information. In view of the demonstrated differences in biometric and weight parameters between the groups of carp studied (Buchtová et al 2006a, b), it is feasible to assume that different nutrition requirements of the fish and different utilization of nutrients received in the diet contributed to the differences in the levels of individual AA found. Even in the same environment and under the same feeding regime, the nutritional requirements of fish of the same age are influenced by their size and degree of sex maturity (Jobling 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations